Fibroblast growth factor-mediated proliferation of central nervous system precursors depends on endogenous production of insulin-like growth factor I. - Drago, J (1991)
Fibroblast growth factor stimulates proliferation and subsequent differentiation of precursor cells isolated from the neuroepithelium of embryonic day 10 mice in vitro. Here we show that fibroblast growth factor-induced proliferation is dependent on the presence of insulin-like growth factors (IGFs) and that IGF-I is endogenously produced by the neuroepithelial cells. Blocking of endogenous IGF-I activity with anti-IGF-I antibodies results in complete inhibition of fibroblast growth factor-mediated proliferation and in cell death. IGF-I alone acts as a survival agent. These observations correlate with the detection of transcripts for IGF-I and basic fibroblast growth factor in freshly isolated neuroepithelium and are consistent with an autocrine action of these factors in early brain development in vivo.